Analys av designalternativ för snabbare dynamik i kolkraftverk med koldioxidavskiljning - Elofsson, David; Höök, Mia; Johansson, Viktor; Mahmoud, Mohammed; Therning, Adam; Öberg, Simon (My University, 2014)
Combustion of fossil fuels is today the dominating source of energy. During combustion, carbon dioxide is formed. The carbon dioxide accumulates in the atmosphere, which raises the global average temperature on earth through the so called greenhouse effect. The only way to reduce the emissions of carbon dioxide from combustion in a coal fired power plant is through carbon capture and storage (CCS). Post-combustion capture is a technology to separate carbon dioxide from the ue gas after the combustion for efficient transport and storage. The steady state operation of coal fired power plants with post combustion capture has already been thoroughly investigated on a pilot scale, however much work remains to investigate the plants dynamic operation. Due to the increasing amount of intermittent energy sources, such as wind and solar power, the energy system will require that the plants that run as base load today will be able to rapidly respond to changes in load. The present work investigates the operation of a coal fired power plant with post combustion capture during load changes. The response rate for different design options has been evaluated and discussed with respect to possible operating scenarios. The investigation does not include economic estimations, even though the importance of capture cost is discussed. According to the modelling it takes 90 to 105 seconds to reduce the electrical output from a power plant with CCS with one percentage point, depending on which load the change is made from. A coal fired power plant without the CCS technology is approximately eight times faster than a power plant with CCS. To increase the response rate of a post combustion system, a method for partial capture of the carbon dioxide was investigated. This method is referred to as CFCC (Constant Flue gas Carbon Capture). This option separates a constant amount of carbon dioxide regardless of the power plant load. In this case the system with CCS will change the load as fast as a power plant without CCS because the amount of ue gas and steam will be kept constant. This option is favorable when the power plant runs on low loads most of the time and increases the load to cover for the peaks in electricity demand. In this case the amount of carbon dioxide captured is less affected by the reduced capture capacity. Another option that was investigated was to temporarily stop the capture unit by reducing the steam extraction to the separation plant to improve the power plant response rate, a method referred to as EDCC (Emergency Dumping of Carbon Capture). In that case a lower degree of separation was accepted during the load changes, making it possible to follow the increased demand on electricity. With this method it is possible for a power plant with CCS to make a load change faster than a power plant without CCS. To stop the capture unit is the fastest way to make a load change of all investigated options. Reducing the steam drain to the separation plant for the short period of time required for the power plant to increase in load has only a slight effect on the overall capture rate.
Keywords: Energi; Kemisk energiteknik; Energy; Chemical energy engineering